Peran Leverage dan Profitabilitas dengan Kebijakan Deviden sebagai Variabel Moderasi terhadap Nilai Perusahaan - Allih Gagah May Suci Sari; Nunung Ghoniyah (Economic Reviews Journal, 2024)
This research aims to examine the influence of leverage, profitability and dividend policy on company value as well as the role of dividend policy in moderating (giving a strengthening or weakening effect) the influence of leverage and profitability on the value of consumer good companies on the Indonesia Stock Exchange in 2021-2023.The population in this research is consumer good companies on the Indonesian stock exchange for the 2021-2023 period with a total of 48 companies. Then a sample of 25 companies in the period 2021-2023 used the purposive sampling method.This research is quantitative research where the data is then analyzed using the multiple linear regression method using moderation test analysis as a tool for measuring relationships. The results of this research show that leverage has a negative and significant effect on company value, profitability has a positive and significant effect on company value, dividend policy has a positive and significant effect on the company and dividend policy has a strengthening effect on the leverage and profitability variables on company value.Dividend policy can be a moderating variable for leverage and profitability on company value. It is known that the R Square value is 0.834, which means that the contribution of the leverage variable and profitability variable to the company value variable after the moderation variable (dividend policy) is 83.4%.So it can be concluded that after the existence of the moderation variable (dividend policy) it can strengthen the influence of the leverage variable and profitability variable on the company value variable.